2023
DOI: 10.1002/agg2.20363
|View full text |Cite
|
Sign up to set email alerts
|

Dicamba off‐target movement from applications on soybeans at two growth stages

Abstract: The objective of this study was to evaluate dicamba off‐target movement during and after applications over soybean at two growth stages. Dicamba‐tolerant soybean [Glycine max (L.) Merr.] at V3 and R1 growth stages in Nebraska and Mississippi fields were treated with diglycolamine salt of dicamba (560 g ae ha−1), potassium salt of glyphosate (1260 g ae ha−1), and a drift‐reducing adjuvant (0.5% v v−1). Filter papers positioned outside the sprayed area were used to determine primary movement and air samplers pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Soybean (Glycine max (L.) Merr.) [7,17,18] Rice (Oryza sativa L.) [19] Cotton (Gossypium hirsutum L.) [20] Peanut (Arachis hypogaea L.) [21] Tomato (Solanum lycopersicum L.) [18,22,23] Lettuce (Lactuca sativa L.) [18] Pumpkin (Cucurbita maxima Duch) [18] Oilseed rape (Brassica napus L.) [18] Pepper (Capsicum annuum L.) [18] Sunflower (Helianthus annuus L.) [18] Cucumber (Cucumis sativus L.) [7] Eggplant (Solanum melongena L.) [7] Snap bean (Phaseolus vulgaris L.) [7] Potato (Solanum tuberosum L.) [24] Sweetpotato (Ipomoea batatas (L.) Lam.) [25] Mandarin (Citrus reticulata) [26] Grapevine (Vitis vinifera L.) [27] Brazilian peppertree (Schimus terebinthifolius Raddi.)…”
Section: Crop Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Soybean (Glycine max (L.) Merr.) [7,17,18] Rice (Oryza sativa L.) [19] Cotton (Gossypium hirsutum L.) [20] Peanut (Arachis hypogaea L.) [21] Tomato (Solanum lycopersicum L.) [18,22,23] Lettuce (Lactuca sativa L.) [18] Pumpkin (Cucurbita maxima Duch) [18] Oilseed rape (Brassica napus L.) [18] Pepper (Capsicum annuum L.) [18] Sunflower (Helianthus annuus L.) [18] Cucumber (Cucumis sativus L.) [7] Eggplant (Solanum melongena L.) [7] Snap bean (Phaseolus vulgaris L.) [7] Potato (Solanum tuberosum L.) [24] Sweetpotato (Ipomoea batatas (L.) Lam.) [25] Mandarin (Citrus reticulata) [26] Grapevine (Vitis vinifera L.) [27] Brazilian peppertree (Schimus terebinthifolius Raddi.)…”
Section: Crop Referencementioning
confidence: 99%
“…In particular, a downwind buffer is required in areas with endangered species concerns, and such distances are increasing in the new labels in order to minimize drift, reduce pesticide exposure, and avoid damaging neighboring crops and non-crop vegetation. Air temperature fluctuations and inversions promote drifting and, therefore, farmers and applicators should avoid sowing their crops in the low parts of their fields and stop spraying early in the morning [8,17]. As Soltani et al [8] suggested, further research is necessary in order to determine the secondary movement of dicamba under various environmental conditions.…”
Section: Crop Referencementioning
confidence: 99%
“…Off-target dicamba movement, in principle, can occur through multiple processes during or after application; ,, among these processes, volatilization of dicamba has been identified as an important pathway for off-target dicamba movement after application. The role of volatilization has been specifically elucidated in field trials, as well as emphasized in a 2021 US EPA report on dicamba off-target movement, which stated that “Officials from numerous states posit that secondary movement, or volatility, is the cause of the majority of off-target incidents.” Although dicamba volatilization remains a persistent problem, efforts have been made to reduce dicamba volatilization by adding additional chemical agents to dicamba formulations. , These agents include amines, which deprotonate dicamba to its nonvolatile anion. , Amines in current dicamba formulations approved for postemergent application include diglycolamine (DGA) and n , n -bis­(3-aminopropyl)­methylamine (BAPMA) salts, which decrease dicamba volatilization relative to dimethylamine (DMA) and isopropylamine (IPA) formulations. Recently, pH buffers have also been added to dicamba formulations to maintain the pH of the formulation solution above the p K a of dicamba (p K a = 1.9) . Although the inclusion of these buffers reduces dicamba volatilization compared to unbuffered solutions, , dicamba volatilization (i.e., after spray application) does not consistently correlate with solution pH, ,, suggesting that other factors beyond pH control of formulation solutions may affect volatilization.…”
Section: Introductionmentioning
confidence: 99%